Giant left ureteric stone - Lal, Vikash; Deolekar, Sandesh; Karandikar, Sangram; Sreedharan, Lokesh (International Journal of Research in Medical Sciences, 2017)
A 24 year old male presented with acute pain in left loin with burning micturition, investigation revealed minimal functioning of left kidney with left hydronephrosis and hydroureter and a giant ureteric calculus. He underwent open ureterolithotomy. A giant ureteric calculus measuring 10.5 cm and weighing 49 gm was retrieved from the left ureter post-operative recovery was eventful and was discharged after 10 days.